Clinical and Immunologic Outcomes After Immediate or Deferred Antiretroviral Therapy Initiation During Primary Human Immunodeficiency Virus Infection: The Sabes Randomized Clinical Study - Javier R. Lama; Rachel Bender Ignacio; Ricardo Alfaro; Jessica Ríos; Jorge A. Gallardo-Cartagena; Rogelio Valdez; Carolyn Bain; Karin Sosa Barbarán; Manuel Villarán; Christopher D. Pilcher; Pedro Gonzáles; Jorge Sánchez; et al. (My University, 2020)
BACKGROUND: In addition to demonstrated public health benefits on reducing transmission, it remains unclear how early antiretroviral therapy (ART) must be started after acquisition of human immunodeficiency virus (HIV) to maximize individual benefits. METHODS: We conducted an open-label randomized clinical study in Lima, Peru among adult men who have sex with men and transgender women with acute (HIV-antibody negative/HIV-1 RNA positive) or recent (confirmed negative HIV-antibody or RNA test within 3 months) HIV infection, who were randomized to start ART immediately versus defer by 24 weeks. We evaluated outcomes by treatment arm and immunologic markers by days since estimated date of detectible infection (EDDI). RESULTS: Of 216 participants, 105 were assigned to immediate arm and 111 to deferred arm (median age 26.8 years, 37% with acute HIV). The incidence of non-ART-related adverse events was lower in immediate versus deferred arm (83 vs 123/100 person-years, IRR 0.67 (95% confidence interval [CI] .47, .95; P = .02), the difference dominated by fewer infections in those treated immediately. After 24 weeks of ART, between-group differences in CD4/CD8 cell ratio lessened (P = .09 overall), but differences between those initiating ART ≤ 30 days from EDDI (median 1.03, interquartile range [IQR] 0.84, 1.37), and those initiating > 90 days (0.88, IQR 0.61, 1.11) remained, P = .02. Principal components analysis of 20 immune biomarkers demonstrated distinct patterns between those starting ART > 90 days from EDDI versus those starting within 30 or 90 days (both P < .001). CONCLUSIONS: To our knowledge, this is the only evaluation of randomized ART initiation during primary HIV and provides evidence to explicitly consider acute HIV in World Health Organization recommendations for universal ART. CLINICAL TRIALS REGISTRATION: NCT01815580.
Keywords: Medicine; Human immunodeficiency virus (HIV); Antiretroviral therapy; Sida; Randomized controlled trial; Immunology; Clinical trial; Virology; Intensive care medicine; Viral disease; Viral load; Internal medicine; Medicine; Human immunodeficiency virus (HIV); Antiretroviral therapy; Sida; Randomized controlled trial; Immunology; Clinical trial; Virology; Intensive care medicine; Viral disease; Viral load; Internal medicine; Sexual and Gender Minorities; Sexual and Gender Minorities; Sexual and Gender Minorities; Sexual and Gender Minorities; Adult; Adult; Adult; Adult; Female; Female; Female; Female; Humans; Humans; Humans; Humans; Male; Male; Male; Male; Peru epidemiology; Peru epidemiology; Peru epidemiology; Peru epidemiology; HIV Infections drug therapy; HIV Infections drug therapy; HIV Infections drug therapy; HIV Infections drug therapy; Homosexuality, Male; Homosexuality, Male; Homosexuality, Male; Homosexuality, Male; CD4 Lymphocyte Count; CD4 Lymphocyte Count; CD4 Lymphocyte Count; CD4 Lymphocyte Count; Anti-HIV Agents therapeutic use; Anti-HIV Agents therapeutic use; Anti-HIV Agents therapeutic use; Anti-HIV Agents therapeutic use; Health Sciences Medicine Infectious Diseases HIV/AIDS Research and Interventions; Life Sciences Immunology and Microbiology Virology HIV Research and Treatment; Life Sciences Biochemistry, Genetics and Molecular Biology Molecular Biology Biological Research and Disease Studies